Suspension of Criminal Proceedings for Perpetrators of Intimate Partner Violence Against Women: Impact on Re-Entries - Vieira-Pinto, Paulo; Muñoz-Barús, José Ignacio; Taveira-Gomes, Tiago; Vidal-Alves, Maria João; Magalhães, Teresa (Frontiers in Psychology, 2021)
Intimate partner violence (IPV) is one of the most prevalent crimes in our society, but the legal mechanisms to oppose it are recent. The Portuguese Provisional Suspension of Criminal Proceedings (PSCP) as a criminal justice system (CJS) response proposes an integrated consensual solution with the involved parties, to reduce offenders’ recidivism. This article analyses the effect of PSCP on re-entries into the CJS. We examined 1,662 IPV police reports, exploring cases that underwent PSCP and re-entries of the same offender in the CJS. Results show that PSCP is applied in 17% of the cases. From all analyzed determinants, with a possible relation to the PSCP implementation, it was found that social violence and the age of both victims and defendants emerge as significantly associated with the request or acceptance of this legal mechanism. No variables tested moderated the relationship between PSCP and re-entry over 96months following the first police report. The article also examined variables that might moderate the decision to request this legal mechanism among victims and defendants.